Design and implementation of an electronic device for reading assistance of printed texts using computer vision for visually impaired people - Rafael Rosales, Cristhian Kevin (2025)
This article presents the design and implementation of an electronic device to assist visually impaired people in reading printed texts. This mechatronic system uses a Raspberry Pi V3 camera mounted on glasses to capture images of printed texts. The images are processed through Optical Character Recognition, and the extracted text is converted to audio using a Text-to-Speech synthesizer, allowing the user to access the visual content audibly. The device is based on a Raspberry Pi 3 Model B+ microcontroller for data management and control of the electronic components. It is designed to be portable, ergonomic, and energy-efficient, with a long-lasting battery.